DIVERSITAS DEWAN DIREKSI DAN PENGARUHNYA TERHADAP KINERJA BANK: STUDI EMPIRIS PADA PERBANKAN DI INDONESIA - Fadli, Jul Aidil; Carolina, Tyasa (School of Accountancy, University of Agung Podomoro, 2021)
The importance of the role of banking for the economy of a country and even the world,demands the skills of the board of directors in the banking industry who are capable of managingcompanies and competing in changing economic situation. Gender diversity, education level andtenure in office will affect the ability of BoD to deal with situations and influence their strategicdecisions. The results show that gender diversity has a negative impact on bank performance, thentenure and education have a positive effect on bank performance. The results of this study provideconsideration for stakeholders in appointing the structure of the board of directors in bankingcompanies.